Integration of Hard, Soft and Mixed Factors for Effective Strategy Implementation: An Eco-System with Strategic Agility Imperative - Nkuda, Matthias O. (NIU Journal of Social Sciences, 2020)
This study focuses on the â€œIntegration of Hard, Soft and Mixed factors for Effective Strategy Implementation: An Eco-System with Strategic Agility Imperative.â€ The purpose was to examine the factors that conduce to effective strategy implementation with particular interest in the human aspects that often contribute to comprise the integrity of or outrightly stall effective strategy implementation.  The investigation was based on desk-research which relied solely on secondary sources of data. Thesis, anti-thesis and synthesis were used as analytical tool. The research found out that many factors are involved in strategy implementation process and each factor has the potential to work for or against effective strategy implementation depending on the factors are streamlined, harmonised and synthesised . These factors classified as hard, soft and mixed need to be properly harnessed under the auspices of strong, capable and visionary leadership to power and drive the strategy implementation via clear communication that builds consensus, commitment, collaborations and vertical and horizontal fits across the organisation. Organisational competencies, reasoned actions of strategy executors and sound knowledge of project management should be leveraged. Grey areas bordering on ulterior motives and corrupt tendencies of strategy executors should be watched out for to be curbed in the bud. It is recommended that business organisations install strategic leaders adept in demands of strategy implementation to help concerned organisations achieve effective strategy implementation within both cost and time and stem the tide of strategy implementation failure . Keywords: Strategy implementation, strategic agility, theory of reasoned action, hard, soft and mixed factors, eco-system.